A measurement of China's new energy vehicle industry using the improved general combined-oriented CCR model. (19th May 2018) - Zhen, Li; Yingqi, Liu
Abstract: R&D plays a vital role in China's new energy vehicle industry. China's central government has attached great importance to the new energy vehicle industry. This paper investigates the R&D efficiency of China's new energy vehicle companies. We collected R&D data from 20 China's new energy auto firms in the year of 2015 and 2016 and established a framework for assessing the technical innovation efficiency, which includes 5 types of variables and 3 types of variables as output indicators. Through using an improved the improved general combined-oriented CCR model, we conducted empirical assessment of technical innovation efficiency, pure technical innovation and scale efficiency for China's major car producers. The results show that most of China's new energy vehicle companies are technical inefficient and generally state-owned enterprises are relatively more efficient than private companies. At last, we proposed some suggestions and advices on how to improve technical innovation efficiency for China's auto makers.